Spectral photosensitivity of the m-n⁰-n structure on the basis of epitaxial layers - Yodgorova, D.M.; Karimov, A.V.; Giyasova, F.A.; Saidova, R.A.; Yakubov, A.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
The results of studies of the spectral characteristics of the m-n⁰-n-structure with a base area on the basis of thin epitaxial specified undoped GaInAs and oxygendoped AlGaAs layers are presented. It is experimentally revealed that own defects and oxygen impurities introduced into the thin active n-area, whose thickness is about the diffusion length, promote the greater photoresponse in the impurity spectral band (1.2 and 1.55 µm). At the same time, impurities present in GaInAs at the background level can be excited, although ineffectively, from the quasineutral part of the active region depleted by the blocking voltage.